Adhesive material property evaluation for improved Lamb wave simulation. (December 2016) - Ong, W.H.; Rajic, N.; Chiu, W.K.; Rosalie, C.
Abstract: Lamb waves are commonly modelled in isotropic metals such as steel and aluminium which have well-known published properties. When attempting to model Lamb waves in polymer materials with viscoelastic properties such as epoxy adhesives, it is not sufficient to rely on published properties which are usually based on quasi-static mechanical testing. This is due to Lamb waves creating an elastic disturbance with a relatively low strain amplitude but high strain rate. Unlike in metals, the modulus of a viscoelastic material is dependent on strain rate. Therefore to accurately model the behaviour of Lamb waves in polymers, the properties of the host structure must be obtained using methods that reproduce the strain amplitudes and strain rates of the intended application. This paper presents an investigation of three ultrasonic methods for determining the material properties of a film adhesive. It is found that the elastic modulus required to accurately model Lamb waves in this adhesive is approximately 60% higher than the value determined by conventional quasi-static testing. Finally, a Lamb wave simulation is used to illustrate that such discrepancies can lead to significant differences in the scattered wave field from a bond-line defect.